Relations between different premedications and hemodynamic changes observed after spinal anaesthesia [FARKLI PREMEDIKASYONLARIN SPINAL ANESTEZI SONRASI IZLENEN HEMODINAMIK DEGISIKLIKLER ILE ILISKISI] - (:unkn) unknown (My University, 1996)
Relations between different pharmacological agents used for premedication and hypotension developed after spinal anesthesia were investigated in this study. Fifty patients divided into five groups each equal in number were included in the study. Premedication was not given to the first group (K). The remaining groups number 2 to 5 received meperidine (M) 1 mg/kg, diazepam (D) 10 mg, fentanyl 0.05 mg plus droperidol 2.5 mg (FD) and chlorpromazine (KI) 25 mg IM respectively. A hundred mg of lidocaine was used for spinal anesthesia. Systolic, diastolic, mean arterial pressures (SAP, DAP, MAP) and heart rate (HR) were noted prior to spinal anesthesia and at 1, 3, 5, 10, 20, 30, 40, 50 and 60 minutes. MAP was found to be low after 50, 1, 20, 60 and 20 minutes in the first to fifth groups respectively (p<0.05). DAP and HR were not changed significantly in the first four groups (p>0.05). In conclusion; hypotension developed during spinal anesthesia can be managed by the guidance of the possible periods determined in our study.
Keywords: Chlorpromazine; Diazepam; Droperidol; Fentanyl; Hypotension; Lidocaine; Meperidine; Premedication; Spinal anesthesia